Clinical profile and pregnancy outcome following tubal recanalisation - S., Vilvapriya; K., Veeraragavan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Female sterilization by tubal ligation accounts for 36% of all methods of family planning used in our country. Almost half of tubal ligations are done in women younger than 25 years. These women want reversal of tubectomy subsequently, in circumstances like death of children, remarriage. This study aims to evaluate various factors affecting the outcome of pregnancies following microsurgical tubal recanalisation. Methods: It is a prospective observational study carried out at Govt Kilpauk Medical College for a total number of 50 patients who have undergone tubal recanalisation during 2011 and 2012. They were followed up till December 2016. Results: 84% of women (n-42) opted for recanalisation were in young reproductive age (<30 years) group. Conception rate was higher in younger age group (52.9% in 21-25 years). Death of children (n-37, 74%) and remarriage (n-12, 24%) were the common indications for tubal recanalisation. Outcome is better if reversal surgery is done within 4 years after sterilization (69.6%, n-16 out of 23) than after 4 years (30.4%, n-7out of 23). Conception rate (55.3%, n-21) was higher and statistically significant in subjects with final length of tube more than 4 cms (P value -0.0193). Conception rate was higher within 1 year of recanalisation (n-13, 26%), followed by 16% (n-8) in 2nd year and statistically significant (p- 0.00001). Overall pregnancy rate in our study was 46% (n-23). Out of the 23 women who conceived, 14 (61%) resulted in live birth, 3 (13%) abortions and the remaining 6(26%) had ectopic pregnancies. Conclusions: Proper selection of patients and meticulous tuboplasty technique can yield successful pregnancy outcome comparable to ART.